Pelatihan Cuci Tangan Pakai Sabun Sebagai Upaya Pencegahan Penyakit Pada Siswa SDK XIV Santo Paulus Bumi Beringin dan SDK XIX Santo Aloysius Tokambene - Florianus Hans Matheus Mawo; Woodford Baren Solaiman Joseph; Amelia Wulan Palopak; Rachel Madeline Frans; Meyvi Irene Safrudib (Jurnal Medika: Medika, 2026)
The practice of clean and healthy living behaviors (PHBS) in schools plays an important role in creating an environment that supports both health and the learning process. One key indicator of PHBS is the habit of washing hands with soap before and after meals. According to the World Health Organization (WHO), effective handwashing consists of six steps: rubbing the palms, the backs of the hands, the spaces between the fingers, the fingertips while clasped, the thumbs with a rotational motion, and the fingertips on the palms. This practice is particularly important for primary school children, who are more vulnerable to illness due to lower levels of personal hygiene. Low awareness among students is often influenced by the lack of education provided at home and school. A preliminary study conducted at SDK XIV Santo Paulus Bumi Beringin and SDK XIX Santo Aloysius Tokambene revealed inadequate handwashing facilities, including the absence of soap, as well as limited student understanding of proper handwashing procedures. This community service activity aimed to improve students’ awareness and skills through educational sessions and hands-on training in handwashing with soap. The results indicated an increase in students’ understanding of the importance of handwashing, their ability to perform the six recommended steps correctly, and their enthusiastic participation throughout the activity. Teachers also demonstrated strong commitment to ensuring the continuity of proper handwashing practices at school. Overall, handwashing training proved effective in fostering clean and healthy living behaviors among primary school students. These findings highlight that adequate facilities, continuous education, and teacher engagement are essential factors in strengthening a culture of hygiene in school environments and in promoting optimal student health